The benefits of an eco-productive green roof in Bogota, Colombia. Issue 8 (October 2017) - Galarza-Molina, Sandra; Torres, Andrés; Rengifo, Pervys; Puentes, Angela; Cárcamo-Hernández, Eliana; Méndez-Fajardo, Sandra; Devia, Carlos
In peri-urban areas of Bogota, people harvest and use untreated rainwater. Initial research indicates that water collected from roofs contains high turbidity values, as well as high concentrations of total suspended solids, biochemical oxygen demand 5-Day and heavy metals. Moreover, these areas do not generally have access to public sewer systems. An eco-productive green roof with the aim of reducing poverty and improving the quality of life of the communities located peri-urban areas of Bogota has been described and examined. These eco-roofs are made with cheaply attainable materials (e.g. recycled plastic bottles). The aim of this study was to understand the hydrological benefits of this type of green roof. We built an experimental set-up consisted of six independent eco-roof modules planted with different crop plant species and a reference roof to serve as a control. The results obtained showed that the crop type had significant influence over the results of both hydrological behaviour and pollutant concentrations measured on the runoff from roofs. The eco-roof can retain up to 65% of the runoff volume and can reduce the runoff peak up to 80%; the eco-roof helped in retaining high concentrations of zinc. The results obtained represent a meaningful positive impact for the eco-roofs tested for stormwater harvesting and suggest that these systems could offer hydrological benefits that might help re-establish hydrological values for marginal urban areas.